The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4172/0974-8369.1000263
|View full text |Cite
|
Sign up to set email alerts
|

Doping in Italy: An Analysis of its Spread in Ten Years

Abstract: Aim: Doping affects the sport. Its explosive spread has triggered the response of sports' and government's institutions. The aims of this study were to know the spread of doping in Italy, what were the most used substances and/or method and in which sports it was more common. Moreover, what instruments were used to contrast it. Methods:We have analysed the doping's spread in Italy since 2003. The data come from the databases of government and sports Italians institutions. We have compared those data and focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Studies placed in SRP employed four different methods for determining prevalence, which were Direct Survey (DS) , Random Response Technique (RT) [102][103][104][105][106][107][108][109][110], Qualitative Interviews (QI) [111], and Network Scale Up (NS) [55]. Studies placed in SAP employed four different methods for determining prevalence, which were Testing Figures (TF) [112][113][114][115][116][117][118][119][120][121], Blood Profile (BP) [122][123][124], Anti-Doping Rule Violations (AD) [125][126][127], and Hair Sample (HS) [79]. One study [79] was found to use a method assigned to SRP and to SAP, thus it was included in both with its two assessment scores included independently in Electronic Supplementary Material Appendix S4.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Studies placed in SRP employed four different methods for determining prevalence, which were Direct Survey (DS) , Random Response Technique (RT) [102][103][104][105][106][107][108][109][110], Qualitative Interviews (QI) [111], and Network Scale Up (NS) [55]. Studies placed in SAP employed four different methods for determining prevalence, which were Testing Figures (TF) [112][113][114][115][116][117][118][119][120][121], Blood Profile (BP) [122][123][124], Anti-Doping Rule Violations (AD) [125][126][127], and Hair Sample (HS) [79]. One study [79] was found to use a method assigned to SRP and to SAP, thus it was included in both with its two assessment scores included independently in Electronic Supplementary Material Appendix S4.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…The law established a particular Committee, "Committee for the Monitoring and Control of Doping and the Protection of Health in Sporting Activities", with the main aim of identifying the classes of prohibited substances and the competitions to be monitored, determining the conduct of anti-doping controls, promoting information campaigns for the protection of health in sporting activities and prevention of doping. Since 2003, every year the above mentioned Committee, elaborates and transmits a report containing detailed data on the spread of doping in Italy as well as activities to prevent and combat the phenomenon (Mazzeo et al 2016a).…”
Section: Original Scientific Papermentioning
confidence: 99%
“…When talking about improving performance, we generally talk about the doping (intentional use by the athletes of drugs or methods aimed at obtaining an improved sports performance beyond the limits possible only with training). There are many studies related to this subject, highlighting the potential health hazards caused by doping [ 19 , 20 , 21 , 22 , 23 , 24 ]. The use of dietary supplements among adolescents raises concerns because of differences between children and adults and the potential for the presence of additives or adulterants in dietary supplement products [ 16 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%